El Niño Modoki can be mostly predicted more than 10 years ahead of time - X. San Liang (Nature Portfolio, 2021)
Abstract The 2014–2015 “Monster”/“Super” El Niño failed to be predicted one year earlier due to the growing importance of a new type of El Niño, El Niño Modoki, which reportedly has much lower forecast skill with the classical models. In this study, we show that, so far as of today, this new El Niño actually can be mostly predicted at a lead time of more than 10 years. This is achieved through tracing the predictability source with an information flow-based causality analysis, which has been rigorously established from first principles during the past 16 years (e.g., Liang in Phys Rev E 94:052201, 2016). We show that the information flowing from the solar activity 45 years ago to the sea surface temperature results in a causal structure resembling the El Niño Modoki mode. Based on this, a multidimensional system is constructed out of the sunspot number series with time delays of 22–50 years. The first 25 principal components are then taken as the predictors to fulfill the prediction, which through causal AI based on the Liang–Kleeman information flow reproduces rather accurately the events thus far 12 years in advance.